miRNAs Flowing Up and Down: The Concerto of Psoriasis - Xiuli, Yang; Honglin, Wang (Frontiers in Medicine, 2021)
Psoriasis is a chronic immune-mediated skin disease, whose hallmarks include keratinocyte hyperproliferation and CD4+ T cell subsets imbalance. Dysregulated microRNAs (miRNAs) identified in psoriasis have been shown to affect keratinocyte and T cell functions, with studies on the molecular mechanisms and intrinsic relationships of the miRNAs on the way. Here, we focus on the dysregulated miRNAs that contribute to the two hallmarks of psoriasis with the miRNA target genes confirmed. We review a network, in which, upregulated miR-31/miR-203/miR-155/miR-21 and downregulated miR-99a/miR-125b facilitate the excessive proliferation and abnormal differentiation of psoriatic keratinocytes; upregulated miR-210 and downregulated miR-138 work in concert to distort CD4+ T cell subsets balance in psoriasis. The miRNAs exert their functions through regulating key psoriasis-associated transcription factors including NF-κB and STAT3. Whether flowing up or down, these miRNAs collaborate to promote the development and maintenance of psoriasis.